A unique intraorbital osseous structure in the large fruit-eating bat (Artibeus lituratus) - Machado, Marcello; Dos Santos Schmidt, Elizabeth Moreira [UNESP]; Margarido, Teresa Cristina; Montiani-Ferreira, Fabiano (Wiley, 2007)
Objective: To describe the normal bony orbital structure of the large fruit-eating bat (Artibeus lituratus) with emphasis on a unique intraorbital bony structure previously not described in the literature. Procedures: The bony anatomy of the orbital cavity was studied on dissected skulls of large fruit-eating bats. The anatomic description of a unique intraorbital spine was made while studying the bony orbit of macerated skulls. Additional observations were made on dissected formalin-fixed whole heads. Both procedures were performed under a stereo dissecting microscope, using ×2-4-magnification. A histologic analysis of soft tissues surrounding this cylindrical bony structure was performed using cross and longitudinal oblique sections from decalcified whole heads, which had been fixed in formalin. Additionally, biometric measurements and a histomorphometric analysis were performed. Results and conclusions: An intraorbital cylindrical osseous structure measuring 3.96 ± 0.68 mm in length and 155.62 ± 14.03 μm in diameter was observed in the large fruit-eating bat (A. lituratus), creating a unique orbital structural design among mammals. We suggest the name optic spine of the alisphenoid bone. The anatomic, biometric and histologic characterization of this element might contribute to a further understanding of the dynamics of bat vision and the sort of factors that influenced evolution of the visual system of microbats. The authors hope that the documentation of this distinctive anatomic feature will also expand the debate about the phylogenetic analysis of the relationship among bat species in the near future. © 2007 American College of Veterinary Ophthalmologists.
Keywords: Alisphenoid; Anatomy; Artibeus lituratus; Bony orbit; Large fruit-eating bat; Ophthalmology; Optic spine; Periorbita; animal; animal disease; bat; biometry; histology; orbit; skull; species difference; visual system examination; Animals; Biometry; Chiroptera; Diagnostic Techniques, Ophthalmological; Orbit; Skull; Species Specificity; Artibeus amplus; Mammalia